S19 The impact of clotting abnormalities on the natural history of idiopathic pulmonary fibrosis: an extended follow up of a population based cohort. (15th November 2016) - Navaratnam, V; Fogarty, AW; McKeever, T; Thompson, N; Jenkins, G; Johnson, SR; Kumaran, M; Pointon, K; Hubbard, RB
Abstract : Background: We have previously demonstrated that people with idiopathic pulmonary fibrosis (IPF) are more likely to have a prothrombotic state and that people with IPF and a prothrombotic state have a higher risk of death at a year's follow up. The aim of this study was to establish the impact of clotting abnormalities on the natural history of IPF with respect to median survival and lung function (forced vital capacity (FVC)). Methods: We recruited 211 incident cases of radiologically diagnosed definite or probable IPF and collected longitudinal information on pulmonary function tests done as part of routine care. All participants were tagged with the NHS Information Centre to enable us to collect data on mortality. Blood samples were tested for a prothrombotic state defined as at least one inherited or acquired clotting defect or marker of fibrinolytic dysfunction. Kaplan-Meir methods were used to calculate median survival. Random effects linear regression modelling was used to estimate decline in FVC. Results: Median follow-up was four years, during which 148 (70.1%) people died. Median survival in those with and without prothrombotic state was 2.7 and 3.7 years respectively (see Figure 1 ). We found evidence of effect modification between risk of death and follow-up time (p = 0.031). There was more than a three-fold increase risk of death in individuals with IPF and a prothrombotic state in the first half of follow-up (HR 3.36, 95% CI: 1.35 to 8.36), but this was reduced (HR 1.79, 95% CI: 1.08 to 2.94) in the second half. The estimated decline in FVC was 288mls (95% CI: 184 to 392mls) in those with normal clotting and 328mls (95% CI: 269 to 387mls) in those with one or more clotting defects. Conclusions: Coagulation dysfunction has an adverse impact on the natural history of IPF, both in terms of median survival and lung function decline. Our findings suggest that a prothombotic state may be a useful biomarker to predict prognosis as part of routine care.